2020
DOI: 10.7554/elife.50580
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary Rab28 and the BBSome negatively regulate extracellular vesicle shedding

Abstract: Cilia both receive and send information, the latter in the form of extracellular vesicles (EVs). EVs are nano-communication devices that influence cell, tissue, and organism behavior. Mechanisms driving ciliary EV biogenesis are almost entirely unknown. Here, we show that the ciliary G-protein Rab28, associated with human autosomal recessive cone-rod dystrophy, negatively regulates EV levels in the sensory organs of Caenorhabditis elegans in a cilia specific manner. Sequential targeting of lipidated Rab28 to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 92 publications
5
51
0
Order By: Relevance
“…The latter case is supported by the relatively mild effects of overexpressing GTP/GDP-preferring mutants of Rab28 and our observation that the nucleotide bound state of Rab28 does not affect interaction with PDE6D, a critical transport regulator of Rab28 (Humbert et al, 2012;Ying et al, 2018). These results are surprising, given the substantial effects of GTP/GDP-binding on both the localization and function of C. elegans RAB-28 that we have previously demonstrated (Jensen et al, 2016;Akella et al, 2020). Our zebrafish data point to the possibility that vertebrate Rab28 is a non-canonical Rab in its behavior and function.…”
Section: Rab28 Localization In Conessupporting
confidence: 51%
See 2 more Smart Citations
“…The latter case is supported by the relatively mild effects of overexpressing GTP/GDP-preferring mutants of Rab28 and our observation that the nucleotide bound state of Rab28 does not affect interaction with PDE6D, a critical transport regulator of Rab28 (Humbert et al, 2012;Ying et al, 2018). These results are surprising, given the substantial effects of GTP/GDP-binding on both the localization and function of C. elegans RAB-28 that we have previously demonstrated (Jensen et al, 2016;Akella et al, 2020). Our zebrafish data point to the possibility that vertebrate Rab28 is a non-canonical Rab in its behavior and function.…”
Section: Rab28 Localization In Conessupporting
confidence: 51%
“…We also note that the background of our transgenic lines includes WT rab28, which may partially ameliorate the effects of overexpression. Given its broad conservation in vertebrates and eukaryotes generally, Rab28 likely acquired this function early in vertebrate evolution, possibly arising from a general role in the shedding of membrane (in the form of extracellular vesicles) from cilia (Jensen et al, 2016;Akella et al, 2020). The recent discovery that ectosome release is a conserved feature of cilia in many different cell-types and species provides an exciting opportunity to discover further regulators of OS shedding and phagocytosis.…”
Section: Loss Of Rab28 Leads To Reduced Cone Os Shedding In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with this hypothesis: in bbs-8 and in che-3 mutants where IFT retrieval of GCY-22-wrmScarlet is reduced, we observed an increased release of GCY-22-wrmScarlet-containing ectosomes (39, 70) ( Figure 8). Previously, bbs-8 mutants were shown to accumulate EVs in an enlarged lumen of the amphid sensilla (47). However, the authors considered these EVs observed in bbs-8 as pathological, since they were not observed in the amphid lumen of control animals.…”
Section: Discussionmentioning
confidence: 97%
“…Worms with disrupted BBSome have been reported to develop slightly truncated cilia revealed by some fluorescent protein markers 19 . However, more recent work by transmission electron microscopy (TEM) demonstrates that in bbs mutants, the overall structure of cilia is very similar to that in wild-type worms, a phenomenon that is very different from mutants lacking some other IFT proteins 37 . At the functional level, the molecular machinery (e.g.…”
Section: Discussionmentioning
confidence: 99%